2010
DOI: 10.1002/pri.495
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between trunk control, respiratory muscle strength and spirometry in patients with stroke: An observational study

Abstract: This study demonstrated that there is a relation between trunk control and respiratory muscular strength, especially concerning the expiratory muscles. However, there seems to be no relation between trunk control and pulmonary function in this series of individuals who suffered stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
3
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 27 publications
7
81
3
6
Order By: Relevance
“…However, other patterns can be observed, such as central neurogenic hyperventilation, apneustic breathing, ataxic pattern, sleep apnea (13,14) and nocturnal hypoxemia (15) . Studies have shown that in addition to the breathing pattern changes, patients affected by stroke may also show decreased ventilatory function (16,17) and respiratory muscle strength (5,8,18) . Changes related to respiratory function which were described in the literature were evaluated by different methods.…”
Section: Major Changes Of the Respiratory System After Strokementioning
confidence: 99%
See 1 more Smart Citation
“…However, other patterns can be observed, such as central neurogenic hyperventilation, apneustic breathing, ataxic pattern, sleep apnea (13,14) and nocturnal hypoxemia (15) . Studies have shown that in addition to the breathing pattern changes, patients affected by stroke may also show decreased ventilatory function (16,17) and respiratory muscle strength (5,8,18) . Changes related to respiratory function which were described in the literature were evaluated by different methods.…”
Section: Major Changes Of the Respiratory System After Strokementioning
confidence: 99%
“…Entretanto, outros padrões podem ser observados como: hiperventilação neurogénica central, respiração apnêustica, padrão atáxico, apneia do sono (13,14) e hipoxemia noturna (15) . Estudos já evidenciaram que além das alterações do padrão respiratório, os pacientes acometidos pelo AVC podem apresentar também redução da função ventilatória (16,17) e da força dos músculos respiratórios (5,8,18) . As alterações relacionadas com a função respiratória descritas na literatura foram avaliadas através de diferentes métodos.…”
Section: Principais Alterações Do Sistema Respiratório Após Avcunclassified
“…More recently, Jandt et al 24 found no correlation between trunk control and inspiratory muscle strength; this correlation was only between EPmax and the expiratory flow with trunk control. In addition we infer that not only flaccid tone interfered with respiratory mechanics, but also that hypertonia and persistent muscle weakness in the trunk muscles exert a negative influence on expiratory muscle strength.…”
mentioning
confidence: 94%
“…In a study on the correlations among respiratory muscles, pulmonary function, and trunk control in stroke patients, Jandt et al 8) reported that the correlations be-tween TIS and MEP was consistent and statistically significant. The correlation between the TIS and MIP was consistent but not statistically significant.…”
Section: )mentioning
confidence: 99%
“…6,7) The effect of a stroke lesion in the respiratory system depends on the structures. 8) Respiratory muscle classify the inspiratory muscles and expiratory muscles. During usual inspiration, the diaphragm and intercostal muscle are the primary muscle that contract.…”
Section: )mentioning
confidence: 99%